(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Nutripreneurs in the Nutrition 4.0 era are learning based on direct experience in the real world which provides opportunities for nutripreneurs to practice entrepreneurship competencies, and "10 top skills 2020-2025" in the context of the challenges of Industry 4.0. Understanding the flow of change towards Industry 4.0 and the impact that has had on "employability standards" for professional workers, about what competencies they must build to prepare themselves for the Industrial 4.0 era. A new standard of the labor market is taking place. New technologies in the Industry 4.0 era create new conveniences as well as new difficulties for humans. Every student should be prepared from an early age to be "robot-proof" or able to adapt to the challenges of change, especially when the role of robots in the workforce will increase and take a larger market share. Prof. Joseph Aoun stated that a person who cannot be defeated by a robot or "robot-proof" is a person with a creative mindset, has the mental elasticity to be able to intentionally find something of value to society. They are figures who are able to compete in the job market where intelligent machines will work alongside humans. They are professionals & entrepreneurs 4.0 who master new literacy, namely: data literacy, technology literacy and human literacy.